Working memory and psychological resilience in South African emerging adults. (December 2020) - Bemath, Nabeelah; Cockcroft, Kate; Theron, Linda
The role of cognitive factors, such as working memory, in psychological resilience has not been widely investigated, although a few studies tentatively suggest a positive association. Given the contextually embedded nature of resilience, sociocultural factors may also influence any relationship between working memory and resilience, and so a concurrent triangulation, mixed method design, located in a socioecological model, was employed to explore this relationship in South African emerging adults from disadvantaged circumstances. A total of 38 participants completed biographical, working memory, and resilience measures. Around 14 of these participants were also interviewed about the perceived role of working memory processes in resilient behaviours. The results suggest that working memory processes indirectly promote resilience-enabling behaviours, while the sociocultural environment also facilitates behaviours which engage working memory and foster resilience. These findings have implications for the development of cognitive-based, resilience-promoting interventions for young adults.